The Romance of Reunion: Montreal War Veterans Return to Family Life, 1944-1949 - Fahrni, Magda (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1998)
AbstractThe narratives of homecoming told during the last years of the Second World War and the first few years of peace drew on the elements of a literary romance: valiant heroes, loyal heroines, and a period of hardship culminating in the hero's triumphant return and the welcoming embrace of the woman he'd left behind. The moment of reunion, however, heralded the beginning of another story: veterans' reintegration into family life in the wake of war and separation. This paper examines the renegotiation of relationships between male war veterans and their spouses, children, and parents. Using Montreal as a case study, it argues that although the family was promoted as an agent of postwar healing, veterans' readjustment to family life was difficult. The fact that war had strained and sometimes shattered relationships was harder to bear given the rhetorical force of the reunion narrative for veterans and their families.